Twenty Years of EU Gender Mainstreaming: Rebirth out of the Ashes? - Hubert, Agnes; Stratigaki, Maria (My University, 2016)
Twenty Years of EU Gender Mainstreaming: Rebirth out of the Ashes? The article looks at the progressive development of gender mainstreaming as a strategy to achieve gender equality in the EU and the role played by policy makers to implement and/or instrumentalise this new concept. From the outset, bureaucracies seized it as an opportunity to dilute the focus on gender and cut resources, transforming its development into a permanent power struggle. The article starts with a brief overview of the major steps and research findings on GM during its launch in the early 1990s and discusses problems arising from related concepts. It then assesses the backlash directed against gender equality, and the demotion of gender mainstreaming, precipitated by the 2004 Eastern enlargement, and the sovereign-debt turned Euro-crisis after 2008. The article concludes by highlighting issues that suggest gender mainstreaming remains the only effective strategy for tackling gender inequalities in the EU, as long as it is understood and implemented in the “policy transformative way”. The article is based on the authors’ insider view stemming from extensive experience in gender equality policies at the European and national level.
Keywords: Europäische Union; Gender Mainstreaming; Gleichstellungspolitik; ddc:303